Malaysian Y generation consumer research: Does gender and technology literacy affirmative towards e-commerce activities? - Kumar M., Dileep; Govindarajo, Normala S; S., Harvi (International Foundation for Research & Development, 2014)
The last two decades have experienced rapid expansion of information and communication technology.This wide application of internet stated its influence on attitude and adoption of internet among various generations.The generation Y which is " the millennial generation " , are the major one who has connected with the technology, especially with internet usage, and is widely in every aspect of life.They adopt technology application in shopping product and services, moving away from traditional purchasing behavior of consumer.Though various studies have come out in the area of generation Y and technology adoption, very less studies are observed connecting gender, and contextualizing the topic to the Malaysian context, considering the consumer internet usage attitude and e-commerce activities. Hence this particular study, then observed and analyzed generation Y attitude towards internet usage and e-commerce activities with its moderating effect of gender variation.